Pengaruh Penempatan Produk Toyota terhadap Kesadaran Merek pada Film â€œNanti Kita Cerita Tentang Hari Iniâ€ - Olivia Nemesis; El Chris Natalia (Lembaga Penelitian, Publikasi dan Pengabdian Masyarakat (LP3M), Institut Komunikasi dan Bisnis LSPR, 2021)
Product placement can be used as a way to promote a product or service. The product or service is displayed in such a way as to give the impression that the product or service is part of a film or TV program. Toyota displays its products in the film â€œNanti Kita Cerita Tentang Hari Iniâ€. â€œNanti Kita Cerita Tentang Hari Iniâ€ is a film with the theme of family. This study aims to determine the influence of Toyota's product placement on brand awareness in the film â€œNanti Kita Cerita Tentang Hari Iniâ€. The research method used is quantitative explanative by distributing questionnaire online. The results show that there is a positive influence between the product placement of Toyota on brand awareness in the film â€œNanti Kita Cerita Tentang Hari Iniâ€. In addition, respondents also agreed that they can identify Toyota as an automotive company and that Toyota's car products are shown without disturbing the respondent's focus while watching the film.